2021
DOI: 10.1161/hypertensionaha.120.16715
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lifetime Classic Psychedelic Use and Hypertension in the Past Year

Abstract: Using data from the National Survey on Drug Use and Health (2005–2014), weighted to be representative of the US adult population, the present study investigated the association between lifetime classic psychedelic use and hypertension in the past year among adults in the United States. The results showed that respondents who reported having used a classic psychedelic at least once in their lifetime had significantly lower odds of hypertension in the past year after adjusting for several potential confounders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 44 publications
(69 reference statements)
6
34
0
Order By: Relevance
“…The results of this national survey-based study showed that lifetime classic psychedelic use was associated with both lower odds of heart disease in the past year and lower odds of diabetes in the past year, which indicates that classic psychedelic use might be beneficial for cardiometabolic health. The findings are novel and build on previous findings on the associations between lifetime classic psychedelic use and various markers of physical health [22][23][24] , but there are several limitations inherent in the study design that merit consideration. First, the crosssectional design used in the present study limits causal inference.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The results of this national survey-based study showed that lifetime classic psychedelic use was associated with both lower odds of heart disease in the past year and lower odds of diabetes in the past year, which indicates that classic psychedelic use might be beneficial for cardiometabolic health. The findings are novel and build on previous findings on the associations between lifetime classic psychedelic use and various markers of physical health [22][23][24] , but there are several limitations inherent in the study design that merit consideration. First, the crosssectional design used in the present study limits causal inference.…”
Section: Discussionmentioning
confidence: 58%
“…The control variables were age in years (18–25, 26–34, 35–49, 50–64, 65 or older); sex (male or female); marital status (married, divorced/separated, widowed, or never married); ethnoracial identity (non-Hispanic White, non-Hispanic African American, non-Hispanic Native American/Alaska Native, non-Hispanic Native Hawaiian/Pacific Islander, non-Hispanic Asian, non-Hispanic more than one race, or Hispanic); annual household income (less than US$20,000, US$20,000–49,999, US$50,000–74,999, or US$75,000 or more); educational attainment (fifth grade or less, sixth grade, seventh grade, eight grade, ninth grade, tenth grade, eleventh grade, twelfth grade, Freshman/13th year, Sophomore/14th year or Junior/15th, Senior/16th year or Grad/Prof School); self-reported engagement in risky behavior (never, seldom, sometimes, or always); lifetime cocaine use; lifetime marijuana use; lifetime 3,4-methylenedioxymethamphetamine (MDMA/ecstasy) use; lifetime phencyclidine (PCP) use; lifetime inhalants use; lifetime other stimulants use; lifetime sedatives use; lifetime pain relievers use; lifetime smokeless tobacco use; lifetime pipe tobacco use; lifetime cigar use; lifetime daily cigarette use; and age of first alcohol use (less than 13 years of age [Preteen], 13–19 years of age [Teen], more than 19 years of age [Adult], or never used). The control variables were coded as separate covariates and were the same as those used in a recent study analyzing the same NSDUH survey years 22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weighted percentage of 0 days of sick leave in the past 30 days was 79% among lifetime classic psychedelic users and 76% among those who did not report lifetime classic psychedelic use (see Simonsson et al, 2021 [ 42 ] for weighted descriptive statistics of characteristics of lifetime classic psychedelic users versus non-lifetime classic psychedelic users).…”
Section: Resultsmentioning
confidence: 99%
“…Findings from clinical research on classic psychedelics are supported by results from cross-sectional studies with nationally representative samples [ 37 , 38 , 39 , 40 ], but more recent cross-sectional research has also found associations between lifetime classic psychedelic use and lower odds of obesity and cardiometabolic diseases in the past year [ 41 , 42 , 43 ]. While causality has not been established, such findings could potentially be explained by healthy lifestyle changes after classic psychedelic use [ 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 96%